Shift Work: A Review and Theoretical Analysis - Dunham, Randall B. (Academy of Management Review, 1977)
A review of research on worker responses to shift work emphasizes identification of workers' problems. Theoretical analysis suggests that many shift-related problems are a function of lack of community orientation toward shift work schedules.